IMAN DAN PERBUATAN DALAM PENGINJILAN JEMAAT MULA-MULA DITINJAU DARI YAKOBUS 2:14-26 - Joko Priyono; Wahyudi Sri Wijayanto (Sekolah Tinggi Teologi Excelsius, 2022)
Evangelism is an inseparable part of the Christian's life. The basis of evangelism is the motivation of “God's love” (John 3:16) or God's concern for those who are lost or lost. In doing so, God uses the means of believers to be channels of blessing to all nations (Gal. 3:9, 14, 29). Meanwhile, the ultimate goal is to establish the Kingdom of God. This shows that evangelism can never be separated from the demonstration of the faith and good works of believers. In this study, the writer aims to find the implications of faith and practice related to the context of early church evangelism in terms of James 2:14-26. The methodological reference that the author uses is biblical studies which include exegesis and Bible studies. According to the study of James 2:14-26, it implies that faith and works cannot be separated from the evangelistic life of Christians. A godly lifestyle and love for all is living evangelism. Because the development of the early church has shown that their quantity increases with the quality of life that shows the way of living the Kingdom of God.Penginjilan adalah bagian yang tidak pernah bisa dilepaskan dari kehidupan orang Kristen Dasar dari penginjilan adalah motivasi “kasih Allah” (Yoh. 3:16) atau kepedulian Allah terhadap mereka yang sesat atau terhilang. Dalam pelaksanaannya Allah memakai sarana orang-orang percaya untuk menjadi saluran berkat bagi semua bangsa (Gal. 3:9, 14, 29). Sementara, tujuan puncaknya adalah mendirikan Kerajaan Allah. Hal ini menunjukkan bahwa penginjilan tidak pernah bisa dilepaskan dari demonstrasi iman dan perbuatan baik orang percaya. Dalam kajian ini penulis bertujuan untuk menemukan implikasi tentang iman dan perbuatan yang dikaitkan dalam penginjilan jemaat mula-mula ditinjau dari Yakobus 2:14-26. Adapun acuan metodologi yang penulis pakai adalah studi biblika yang mencakup eksegesis dan kajian Alkitab. Menurut kajian Yakobus 2:14-26 memberikan implikasi bahwa iman dan perbuataan tidak bisa dilepaskan dari kehidupan penginjilan orang Kristen. Gaya hidup saleh dan kasih kepada semua orang merupakan penginjilan yang hidup. Sebab dari perkembangan jemaat mula-mula telah memperlihatkan bahwa kuantitas mereka bertambah seiring kualitas hidup yang menunjukkan cara hidup Kerajaan Allah.